Beautiful darkness - Garcia, Kami.; Stohl, Margaret (New York : Little, Brown, 2010)
In a small southern town with a secret world hidden in plain sight, sixteen-year-old Lena, who possesses supernatural powers and faces a life-altering decision, draws away from her true love, Ethan, a mortal with frightening visions.
Keywords: Supernatural -- Young adult fiction; Psychic ability -- Young adult fiction; Love -- Young adult fiction; South Carolina -- Young adult fiction